Effects of caffeine, ephedrine and their combination on time to exhaustion during high-intensity exercise - Bell, D. G.; Jacobs, I.; Zamecnik, J. (European Journal of Applied Physiology, 1998)
This study investigated the effects of acute ingestion of caffeine (C), ephedrine (E) and their combination (C+E) on time to exhaustion during high-intensity exercise. Using a repeated-measures, double-blind design, eight male subjects exercised on a cycle ergometer at a power output that led to exhaustion after about 12.6 min during a placebo (P) control trial. They did this 1.5 h after ingesting either C (5 mg · kg-1), E (1 mg · kg-1), C+E, or P. Trials were separated by 1 week. Venous blood was sampled before and during exercise. The mean (SD) times to exhaustion were 12.6 (3.1) (P), 14.4 (4.1) (C), 15.0 (5.7) (E) and 17.5 (5.8) (C+E) min. Only the C+E treatment significantly increased time to exhaustion compared to P. Oxygen consumption (V˙O2), carbon dioxide production (V˙CO2), minute ventilation (V˙E) and the respiratory exchange ratio (RER) were similar during exercise for all trials. Heart rate during exercise was significantly increased for the C+E and C trials compared to P. Subjective ratings of perceived exertion during exercise were significantly lower after C+E compared to P. All treatments significantly increased lactate levels. Free fatty acid (FFA) levels were significantly increased by C ingestion. Glycerol levels were increased by C+E and C ingestion. Glucose levels were also higher with the drug treatments compared to P. Increased monamine availability after C+E treatment was suggested by measurements of catecholamines and dopamine. In conclusion, the combination of C+E significantly prolonged exercise time to exhaustion compared to P, while neither C nor E treatments alone significantly changed time to exhaustion. The improved performance was attributed to increased central nervous system stimulation.